2013
DOI: 10.1038/nrc3539
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box proteins: tuning forks for transcriptional harmony

Abstract: Forkhead box (FOX) proteins are multifaceted transcription factors that are responsible for fine-tuning the spatial and temporal expression of a broad range of genes both during development and in adult tissues. This function is engrained in their ability to integrate a multitude of cellular and environmental signals and to act with remarkable fidelity. Several key members of the FOXA, FOXC, FOXM, FOXO and FOXP subfamilies are strongly implicated in cancer, driving initiation, maintenance, progression and drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
607
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 599 publications
(622 citation statements)
references
References 191 publications
11
607
0
4
Order By: Relevance
“…The G 2 -M arrest observed can be because of the fact that FOXO3a negatively regulates the expression of genes, including cyclin B and FOXM1 ( Fig. 1A) important for G 2 -M progression (2,36). Collectively, these data suggest that dexamethasone arrests cell-cycle progression, particularly in G 2 -M phase, and induces cell death in the sensitive but not resistant B-ALL cells.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The G 2 -M arrest observed can be because of the fact that FOXO3a negatively regulates the expression of genes, including cyclin B and FOXM1 ( Fig. 1A) important for G 2 -M progression (2,36). Collectively, these data suggest that dexamethasone arrests cell-cycle progression, particularly in G 2 -M phase, and induces cell death in the sensitive but not resistant B-ALL cells.…”
Section: Discussionmentioning
confidence: 67%
“…It is well-established that Akt (PKB)-mediated phosphorylation and inactivation of FOXO3a culminate in cytoplasmic localization and cell proliferation (2,3). Herein, we showed that in the sensitive B-ALL cell lines, RS4,11 and SUP-B15, FOXO3a became dephosphorylated on Akt-targeted sites, Ser253, Thr315, and Thr32 upon dexamethasone treatment, but its phosphorylation was unaffected by dexamethasone in the resistant REH cells.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Recent whole genome analysis identified a GATA3 mutation which exists in 14% of luminal A breast cancer [35]. It was reported that ERα, FOXA1 and GATA3 form a functional enhanceosome to drive the transcription of ERα-regulated genes in breast cancer cells [36,37]. High FOXA1 and GATA3 expression might therefore affect endocrine responsiveness and prognosis in ER-positive breast cancer [38].…”
Section: Discussionmentioning
confidence: 99%